The Impact of COVID-19 Lockdown on People With Epilepsy and Vagal Nerve Stimulation - Grande, Eleonora; Tufo, Tommaso; Ciavarro, Marco; Di Muccio, Ines; Fuggetta, Filomena; Silvestri, Martina; Bevacqua, Giuseppina; Lanzone, Jacopo; Assenza, Giovanni (Frontiers in Neurology, 2021)
Objectives: Restrictive measures adopted during the COVID-19 pandemic, in order to limit contagion, had a severe impact on mental health. The burden of lockdown was particularly heavy on patients with chronic neurologic diseases such as People with Epilepsy (PwE). Our survey wants to describe the struggles and needs of Drug-Resistant (DR) PwE with implanted Vagal Nerve Stimulator (VNS) during the first wave of COVID-19 lockdown, in order to find strategies that help patients cope with present or future periods of restriction. Methods: We collected answers from 30 respondents, who underwent an online survey including socio-demographic and clinical information and COVID-19 related information. Depression, anxiety symptoms and sleep quality were investigated in patients through BDI II, GAD-7 and PSQI scale. Results: 46% of our sample reported increase in the number of seizures; the entire sample complained epilepsy-related issues (medication availability, VSN adjustments, anxiety, sleep disturbance); one out of three participants reported major epilepsy issues felt like urgent; 30% had to postpone scheduled examination. Significative higher scores for depression and anxiety scales were found in patients who perceived seizure frequency worsening and reported major epilepsy-related issues. Conclusion: Preliminary finding showed that the first lockdown influenced the clinical and psychological status of PwE and was related with seizure worsening. The lack of medical assistance and control on VNS therapy left patients to cope with the situation without chance to contact a specialist. We discuss how a wider implementation of telemedicine programs could facilitate remote assistance of PwE with a VNS implant.